Review of Blade Materials for IGT. (2015) - Peng, J.Q.; Zhang, H.T.; Li, Y.F.
Abstract: In this paper, the development process of superalloy material was reviewed with focus on the material property requirements for the turbine blade of Industrial Gas Turbine (IGT). The chemical compositions and mechanical properties were also discussed for the typical alloys of the turbine blades.